Induced Abortion: A Risk Factor for Adenomyosis - Pun, Sunita (Journal of Nepal Health Research Council, 2023)
Background: Abortion, the medical and surgical termination of a pregnancy,is becoming a more common medical procedure among women in Nepal. Adenomyosis is one of the common gynecological problems among women of reproductive age. However, little is known about the relationship between abortion and adenomyosis. Therefore, our study aims to explorerisk factor for adenomyosis in among women who havehadabortions.Methods: A comparative study was carried out among women who visited at thedepartment of Obstetrics and Gynecologyof the Tribhuvan University of Teaching Hospital, Kathmandu, between 13th April 2016 to 14th July 2017. Adenomyosis were confirmed through histological examination after hysterectomy. Data wereanalyzed by using Statistical Package for Social Sciences (SPSS software)21.0 version. Odd ratio with their 95% confidence interval and P-value were calculated and analyzed. A P-value equal or below 0.05 was considered as statistically significant.Results: Of the total 255 women, 85were confirmed adenomyosisby histological examination. Of the 85 cases, 39% (33/85) had a history of abortion, while only 25 % (44/170)women had abortion among non-adenomyosis group. Overall, women who had abortion were1.8 timesmore likely to have adenomyosis (95% CI 1.04- 3.17, P value=0.03) compared to women who had no history of abortion. Women with surgical abortions were 2.5 times more likely to develop adenomyosis (95% CI- 1.03- 6.21, P value=0.03) compared towomen with no abortion history.Conclusions: This study found that women,who had abortions,aremore likely to have been diagnosed with adenomyosis compared to women without abortions.Further studies, however, need to be carried out in order toextend findings of this study. Keywords: Abortion; adenomyosis; risk factors